Deconstruction of Characters in the Film Di Bawah Lindungan Ka’bah - Elmustian; Anisah Dzakirah (International Journal of Technology and Education Research, 2026)
This study aims to examine the deconstructionist view of the characters in the film “Di Bawah Lindungan Ka’bah”by director Hanny R. Saputra, which is a transformation of the novel by Buya Hamka. The purpose of this study is to describe the deconstructionist view of the characters in the film “Di Bawah Lindungan Ka’bah”. This study uses a descriptive qualitative method with Jacques Derrida's theory. The data in this study comes from the film “Di Bawah Lindungan Ka’bah” which is analyzed to find the deconstruction of the characters' characters. The results show that there is a hidden reality of the characters in the film Under the Protection of the Ka'bah. The deconstructionist view in this study is used to dismantle the meaning that seems certain in the audience's view. The results of the study found that there is a meaning that is removed from the surface view of the characters. The deconstructionist view proves that the characters in the characters cannot be viewed stably with the image of the protagonist and antagonist. Some characters depicted as protagonists, apparently have hidden realities, while some characters depicted as antagonists also have hidden facts from their characters